CAR-T cells for cancer immunotherapy—the barriers ahead and the paths through. (21st October 2022) - Zhang, Qiqi; Zu, Cheng; Hu, Yongxian; Huang, He
Abstract: This review discusses the major concerns and changes emerged during the rapidly extended clinical application of chimeric antigen receptor (CAR) T therapy based on our experience and understanding. In the past decades, the CAR-T cells have been questioned, sequentially, about their capability of inducing initial remission, their safety profile, their ability to sustain long-term persistence and response, and their potential to be industrialized. Significant advances, novel targeting strategies, innovative molecular structure, fine tuning of both CAR-T and host immune system, combination with other therapies, streamlined manufacturing, and etc., have been made to overcome these challenges. Although not perfectly resolved, rational pathways have been proposed to pass through the barriers. Here, we present the recent achievements on these pathways, and look into the possible future directions.